2020
DOI: 10.1002/cncr.33135
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and clinicopathologic associations of DNA mismatch repair protein deficiency in ampullary carcinoma: Routine testing is indicated

Abstract: BACKGROUND: The significance of DNA mismatch repair (MMR) deficiency in ampullary cancers (ACs) has not been established. METHODS: In total, 127 ACs with invasive carcinomas measuring ≥3 mmthat had adequate tissue were analyzed immunohistochemically. RESULTS: MMR loss was detected in 18% of ACs (higher than in colorectal cancers). Twelve tumors with MLH1-PMS2 loss were negative for BRAF V600E mutation, suggesting a Lynch syndrome association. MMR-deficient tumors (n = 23), comparedwith MMR-intact tumors (n = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…In western AMPAC patients, the incidence of MMR-deficiency (MMRd) was higher than those with colorectal cancer. Previous studies found that 18% (23/127) of western patients with AMPAC had MMRd as evaluated by IHC [ 34 ]. However, in current study, we only identified two AMPAC patients (1.38%) with MSI-H, which was significantly lower than the incidence in the western patients (8.75%, p < 0.01) [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In western AMPAC patients, the incidence of MMR-deficiency (MMRd) was higher than those with colorectal cancer. Previous studies found that 18% (23/127) of western patients with AMPAC had MMRd as evaluated by IHC [ 34 ]. However, in current study, we only identified two AMPAC patients (1.38%) with MSI-H, which was significantly lower than the incidence in the western patients (8.75%, p < 0.01) [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Biliary tract cancers may harbor mismatch repair gene mutations which may explain the associations with colon and pancreatic cancers [26,27]. Recently, these mutations have also been found in ampullary cancer [34]. The association of ampullary cancers with male breast cancer may be related to BRCA1/2 mutations which are found in this cancer [35].…”
Section: Discussionmentioning
confidence: 99%
“…The damaged mismatch repair system (MMR deficiency) for DNA, including the alteration in the MLH1 , MSH2 , or MSH6 gene, could cause MSI. However, MMR deficiency often has a Lynch-suggestive profile, and routine testing for Lynch syndrome is warranted ( 29 ). MSI may be a dependable marker for prognosis.…”
Section: Molecular Classification Associated With Clinical Outcomesmentioning
confidence: 99%
“…AVC patients with MSI phenotypes who underwent resection therapy had no evidence of recurrent disease at the cutoff time in a study of 59 patients ( 65 ). The AVC patients ( 29 ) with MMR deficiency accounted for up to 18% (23/128). Regarding the relationship between histological subtypes and MSI, a study reported that both AVC patients with MSI had the intestinal subtype of AC ( 65 ).…”
Section: Molecular Classification Associated With Clinical Outcomesmentioning
confidence: 99%